(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Maintenance of tidal turbines is expensive, and relies upon suitable weather conditions and vessel availability, which can lead to costly delays. Turbine reliability can be improved by eliminating complexity in the design. The use of fixed-pitch blades, for example, can greatly reduce maintenance costs by avoiding complex active blade-pitch mechanisms which are the main source of failure in wind turbines. Pitching rotor blades to feather in high-flow conditions is, however, the most effective means of reducing loads on the rotor. Turbines with fixed-pitch blades therefore necessarily have smaller rotor diameters compared to those with active-pitch systems, in order to keep the thrust force, flap-wise bending moment, and power output within allowable limits. In low-flow conditions, power output is proportional to the square of the rotor diameter, so turbines with small diameter rotors capture less energy over their lifetime. This study seeks to develop a novel passive-pitch mechanism for tidal turbine blades. This mechanism must be reliable, and should act to reduce the loads on the rotor in high-flow conditions so that a larger diameter rotor can be installed, increasing power capture. An initial design for a passive-pitch mechanism, which is actuated by the hydrodynamic forces developed by the rotor such that the blades pitch-to-feather in high-flow conditions, has been developed. The design is compatible with proven passive reversible rotor blade technology, eliminating the requirement for a maintenance sensitive yaw mechanism. Since initial concept design, work has been undertaken to build a tool, based on NREL’s OpenFAST blade element momentum code, which models the forces acting on the rotor blades, coupled with the mechanical response of the passive blade-pitch mechanism. This tool has been used to predict the performance of the turbine for a range of operating conditions, allowing the influence of parameters such as blade geometry, rotor diameter and passive-pitch response to be analysed in terms of rotor loading and turbine performance. Initial analysis suggests that installing blades with a passive-pitch mechanism could reduce the loads on the rotor in high-flow conditions down to just 25% of the loads that would act on an equivalent rotor with fixed-pitch blades. This would allow larger diameter rotors to be installed which could improve annual energy yield by over 40% at a typical site. Despite these significant potential performance improvements, the challenges of developing a passive blade-pitch mechanism for tidal turbines are not well understood, as tidal developers have all so far implemented fixed or active pitch mechanisms. These challenges will be addressed throughout the remainder of this study, which will involve detailed design followed by physical tank testing.